Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper for Indonesia uses a small structural macroeconomics model of the Indonesian economy to analyze the inflation outlook and monetary policy challenges. The Bank of Indonesia (BI) introduced its Inflation Targeting Framework in July 2005 with the goal to reduce inflation in the medium term to 3 percent. BI's official mandate is stability of the rupiah, both internal and external, and BI views the inflation targeting regime with a floating exchange rate as the best strategy to fulfill that mandate.